"Справа лікарів" у Чернівцях - Безаров, Олександр Троянович (Актуальні питання суспільних наук та історії медицини. Спільний українсько-румунський науковий журнал., 2024)
The aim of research is to determine the circumstances of the development of the «Doctors’ Case» in Chernivtsi at the beginning of 1953, to find out the facts and nature of the persecution of Jewish doctors in Chernivtsi during the specifi ed period of history. Research methods. Comparative- historical, problem chronological and statistical methods of research have been applied. Scientifi c novelty. It is known that the «Doctors’ Case» is a socio- political provocation by the Stalinist leadership of the USSR and Y. V. Stalin personally, which was initiated by a corresponding report in the newspaper «Pravda» dated January 13, 1953 about Kremlin doctors who were allegedly preparing the murder of the Soviet and party leaders of the USSR. During the falsifi cation of the «Doctors’ Case», anti- Semitic propaganda spread widely in the country, because, as it turned out, there were many Jews among the doctors and medical workers. «Doctors’ Case» was stopped immediately after the death of Y. V. Stalin, and its participants were rehabilitated. In Chernivtsi, as a result of the «Doctors’ Case», the employees of the Chernivtsi Medical Institute suff ered the most: they were fi red from their jobs in early 1953 or forced to resign at their own will. For example, on January 29, 1953, at the meeting of the Academic Council of Chernivtsi Medical Institute, the head of the Department of Hospital Surgery, professor, a famous Jewish Doctor O. Yu. Mannheim, was chosen as the target for disclosure of «anti- Soviet activities». Soon he was forced to resign from his position and hide from the persecution of the state security authorities. On March 5, 1953, the Associate Professor of the Department of Obstetrics and Gynecology I. V. Krasnianskyi was dismissed. R. L. Buks, N. M. Shinkerman, B. I. Kratsfeld, M. D. Pekarskyi, A. M. Pekhovych, Ya. D. Krychyn, L. V. Kriger, D. A. Gulman, O. B. Makarevych, S. E. Shmukler, M. Yu. Rapoport, F. G. Tabak, R. L. Roth- Hokhshet, E. L. Shkolnik and other Jewish employees of Chernivtsi Medical Institute resigned from their positions. In some medical institutions of the city, in particular, in Chernivtsi Sanitary Station, meetings of the labor team were held, at which the participants «angrily condemned» the «non- Russian» «gang of murderers» in white coats. Corresponding «protest actions» were also organized in pre-school institutions of the city, since Jewish teachers in kindergartens were allegedly involved in the «criminal conspiracy» of Jewish doctors. Conclusions. The author analyzed a number of unpublished documents, as a result of which the conclusion was formulated that in Chernivtsi the «Doctors’ Case» did not gain a special public response and support from the local authorities, and therefore, was not accompanied by mass repressions against Jewish doctor.
Keywords: doctors, Jews, anti- Semitism, Stalinism, Chernivtsi, Chernivtsi Medical Institute